2022
DOI: 10.55385/kastamonujes.1185210
|View full text |Cite
|
Sign up to set email alerts
|

Change of Calcium Concentrations in Forest Soils by Plant Species and Soil Depth

Abstract: One of the most important factors playing role in plant development is the nutrient element content of the soil. Being one of the fundamentally necessary macronutrients for plant nourishment, calcium (Ca) plays an important role in the growth and development of a plant. Thus, even though many studies have been carried out on the change of Ca concentration in agricultural soils, the number of studies examining this subject for forest soils is very limited. In the present study, it was aimed to compare the conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…As a result of a study conducted on seven different species determined that the Cu and Cd concentrations in the branches were higher than in the leaves (Mossi, 2018). In another study conducted in four different species, the minimum K values were found in the branches, the Cd value in the seed, and the highest concentration for K and Cd were found in the seed and leaves, respectively (Erdem, 2018). However, other organs are also used extensively in monitoring element concentrations, and the variation of heavy metal concentrations based on the organ is one of the most frequently discussed issues.…”
Section: Discussionmentioning
confidence: 95%
“…As a result of a study conducted on seven different species determined that the Cu and Cd concentrations in the branches were higher than in the leaves (Mossi, 2018). In another study conducted in four different species, the minimum K values were found in the branches, the Cd value in the seed, and the highest concentration for K and Cd were found in the seed and leaves, respectively (Erdem, 2018). However, other organs are also used extensively in monitoring element concentrations, and the variation of heavy metal concentrations based on the organ is one of the most frequently discussed issues.…”
Section: Discussionmentioning
confidence: 95%
“…In a study conducted by [50], it was determined that concentrations of Pb, Ca, Fe, Cr, Zn Cu, Ca, Ni, and Mn increased in eight plant species due to traffic density. But heavy metals were also seen to be retained differently depending on the plant characteristics [51,52]. Finally, the results of one study [53] showed that HM concentrations vary significantly not only among different species but also among different organelles of the same species.…”
Section: Discussionmentioning
confidence: 97%
“…Heavy metal concentrations, especially in the inner barks, are primarily related to entering heavy metals into the tree tissue. Heavy metals enter the tree tissue mainly through stem parts, leaves, and roots [30].…”
Section: Discussionmentioning
confidence: 99%